Application of Fuzzy Control to a Sonar-Based Obstacle Avoidance Mobile Robot - Tang, Quốc Nam; Dao, Văn Hiệp (Journal of Technical Education Science, 2008)
This paper describes how fuzzy control can be applied to a sonar-based mobile robot. Inputs of the fuzzy controller are distances between left, right sonar and object(s); output is rotation angle to avoidance the obstacle(s). The robot controller is implemented under the behavior-based approach with an individual priority levels. The experimental results show that behavior of the robot are correct, the robot can simultaneously implements motion tasks, avoids obstacles and can react in case of emergency.